Evaluating Time to In-Hospital Venous Thromboembolism in Obese Patients. (April 2021) - Cutshall, B. Tate; Tatara, Alexandra W.; Upadhyay, Navneet; Adeola, Mobolaji; Putney, David; Ruegger, Melanie
Background: Currently, no consensus approach exists for optimal venous thromboembolism (VTE) prophylaxis in obese (BMI ≥30 kg/m 2 ) patients. Time to development of in-hospital VTE is not well studied. Objective: This study evaluates time to in-hospital VTE in obese patients. Methods: A single-center, retrospective study evaluated obese patients that developed an in-hospital VTE. Patients were categorized into 3 BMI groups: 30 to 34.9 (group 1), 35 to 39.9 (group 2), and ≥40 (group 3) kg/m 2 . The primary end point compared time to VTE between the groups. Results: A total of 246 patients were included, and time to VTE was similar between the groups, 8 (group 1) versus 8 (group 2) versus 9 days (group 3); P = .38. Secondary outcomes showed time to VTE was shorter in acute care versus ICU patients (7.5 vs 10 days; P = .01), nonsurgical versus surgical patients (6 vs 9 days; P = .004), and no prophylaxis versus mechanical plus pharmacologic prophylaxis (4.5 vs 9 days; P < .001). Conclusions: BMI category did not significantly impact time to in-hospital VTE. This study provides insight into the timing of in-hospital VTE in obese patients. The differences in prophylactic strategies highlight the importance of optimized prophylaxis.